2018
DOI: 10.1016/j.jval.2018.04.185
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Niraparib and Olaparib as Maintenance Therapy for Patients with Platinum Sensitive< Recurrent Ovarian Cancer

Abstract: S29third-party payer's analysis. ReSultS: Incremental QALYs for Regorafenib compared to BSC was 0.12 (0.51 vs 0.39).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 0 publications
1
39
0
4
Order By: Relevance
“…Similarly, poly (ADP-ribose) polymerase inhibitors have demonstrated an impressive increase in PFS in BRCA mutation carriers, but OS data are not mature (4). Furthermore, these therapeutic approaches are extremely costly (5)(6)(7)(8)(9). Thus new, cost-effective approaches are needed to reduce relapse rates for patients with EOC and improve OS.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, poly (ADP-ribose) polymerase inhibitors have demonstrated an impressive increase in PFS in BRCA mutation carriers, but OS data are not mature (4). Furthermore, these therapeutic approaches are extremely costly (5)(6)(7)(8)(9). Thus new, cost-effective approaches are needed to reduce relapse rates for patients with EOC and improve OS.…”
Section: Introductionmentioning
confidence: 99%
“…È interessante rilevare che la PFS è raccomandata come endpoint primario (ritenuto maggiormente informativo della sopravvivenza totale a partire dalla terza linea di trattamento) negli studi clinici aventi per oggetto l'efficacia dei PARPi nel CO, poiché questi includono pazienti che, pretrattate con diversi regimi chemioterapici, rappresentano, di fatto, una popolazione eterogenea. 56 Pur con le note cautele che debbono caratterizzare il confronto con studi di carattere economico sanitario condotti all'estero, 57 a motivo, ad esempio, delle differenze nelle modalità di valorizzazione delle risorse sanitarie, i costi unitari di gestione delle medesime tossicità ematopoietiche rilevati nei due studi statunitensi precedentemente citati, 12,14 Vi è inoltre da considerare che, secondo alcuni Autori, 10 in questa indicazione terapeutica, l'incidenza della neutropenia di grado severo, febbrile e non febbrile, risulta più elevata (0,432) negli RCTs che prevedono la combinazione di olaparib e chemioterapia verso chemioterapia, 21 rispetto ad analoghe esperienze di ricerca volte a sperimentare olaparib in monoterapia verso placebo, che riportano valori di incidenza compresi tra lo 0,037 e lo 0,10. 58,59 Pertanto, per quanto concerne l'incidenza della neutropenia di grado severo per olaparib, il modello di valutazione economico-sanitaria ha adottato un'ipotesi di ricerca sfavorevole a tale principio attivo.…”
Section: Discussione E Conclusioniunclassified
“…9 Per quanto attiene al profilo di tollerabilità, una caratteristica comune ai diversi PARPi è la frequenza di tossicità ematopoietiche (anemia, neutropenia, trombocitopenia), variabili in monoterapia o in associazione con chemioterapia, l'incidenza delle quali si qualifica, inoltre, per un'apprezzabile variabilità tra le diverse esperienze di ricerca. 6,10 Tra le principali conseguenze cliniche delle tossicità ematopoietiche da PARPi, si annoverano la riduzione della posologia 11 e la dilazione delle successive somministrazioni della terapia, 12,13 con possibili riflessi sulla gestione della neoplasia sottostante e, dunque, sulla sopravvivenza della paziente.…”
Section: Introduzioneunclassified
“…Additionally, although PARPi have extended patients' progression-free survival in the clinical trial setting, they are also associated with high costs. For instance, in 2017, a 30-day supply of olaparib amounted to $13,000, plus additional costs for therapy monitoring and management of adverse events [86]. To investigate the benefit of adding PARPi therapies that are efficient -to a certain point, as resistances are common and develop through multiple mechanisms -but also costly and toxic, researchers have performed studies on their cost-effectiveness [86,87].…”
Section: Potential Of Applying This Knowledge To Canine Mammary Tumormentioning
confidence: 99%
“…For instance, in 2017, a 30-day supply of olaparib amounted to $13,000, plus additional costs for therapy monitoring and management of adverse events [86]. To investigate the benefit of adding PARPi therapies that are efficient -to a certain point, as resistances are common and develop through multiple mechanisms -but also costly and toxic, researchers have performed studies on their cost-effectiveness [86,87]. In 2018, Zhong et al showed that olaparib and niraparib may not be cost-effective treatments; indeed, they determined an ICER value (Incremental Cost-Effectiveness Ratio, a statistic tool which summarizes the additional cost of an outcome gained by one intervention compared with another) of $250,000 per PFS (Progression-free survival) life-year [86].…”
Section: Potential Of Applying This Knowledge To Canine Mammary Tumormentioning
confidence: 99%